Interactive AR Book As Media For Educating Children About Colorism in Jakarta - Vera Jenny Basiroen; Damba Permatasakti; Renalda Elnesia Paath (ULTIMART Jurnal Komunikasi Visual, 2022)
The obsession with skin whiteness as a symbol of beauty has long been rampant in the Asian continent, including Indonesia. During the colonial period in Indonesia, white women had become beauty icons, as shown in old magazines. Research and the media have shown that colorism remains largely ignored in the modern era. This study aims to find an effective way to educate the younger generation about the problem of colorism. The research target was limited to the city of Jakarta by observing and interviewing six to eight-year-old students at two local schools in the South. The methods used in this study were interviews with child psychology experts and focus group discussions with the target market. The results show that the stigma of colorism exists among children in big and modern cities like Jakarta. There is a need for education and triggering action on this issue. Using an interactive children’s AR book can be an educational and emotional tool for understanding colorism. AR features deepen the story through animated illustrations and increase interaction with readers. Keywords: colorism; educating; children; AR book; illustration